Sediment Matters - Heininger, Peter (Springer, 2015)
This book presents insights into the complex processes controlling sediment behavior in river basins and into state of the art integrated sediment management concepts. Main topics are: sediment transport, modelling sediment transfer in rivers, sediment quality, sediment monitoring and integrated sediment management at catchment scale. Interlinkages of sediment dynamics and quality with biogeochemistry, ecology, climate change and human activities are discussed. Drivers, boundary conditions and processes of erosion, sediment transport and sedimentation are presented with the aim to help the reader putting sediment quantity and quality issues into perspective.